Оптимізація реабілітаційних програм в санаторних умовах у пацієнтів первинним гонартрозом зі зниженною мінеральною щільністю кісткової тканини = The rehabilitation programs optimization in sanatorium in patients with primary gonarthrosis with decreasing of bone mineral density - Bakalyuk, T. G. (Journal of Education, Health and Sport, 2016)
Bakalyuk T. G. Оптимізація реабілітаційних програм в санаторних умовах у пацієнтів первинним гонартрозом зі зниженною мінеральною щільністю кісткової тканини = The rehabilitation programs optimization in sanatorium in patients with primary gonarthrosis with decreasing of bone mineral density. Journal of Education, Health and Sport. 2016;6(3):125-139. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47940 http://ojs.ukw.edu.pl/index.php/johs/article/view/3429 https://pbn.nauka.gov.pl/works/721332 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. УДК 616.728.3-06:616.748-007.234]-085.838 THE REHABILITATION PROGRAMS OPTIMIZATION IN SANATORIUM IN PATIENTS WITH PRIMARY GONARTHROSIS WITH DECREASING OF BONE MINERAL DENSITY T. G. Bakalyuk I.Ya. Gorbachevsky Ternopil State Medical University, Ternopil, Ukraine ОПТИМІЗАЦІЯ РЕАБІЛІТАЦІЙНИХ ПРОГРАМ В САНАТОРНИХ УМОВАХ У ПАЦІЄНТІВ ПЕРВИННИМ ГОНАРТРОЗОМ ЗІ ЗНИЖЕННОЮ МІНЕРАЛЬНОЮ ЩІЛЬНІСТЮ КІСТКОВОЇ ТКАНИНИ Т. Г. Бакалюк ДВНЗ “Тернопільський державний медичний університет імені І. Я. Горбачевського МОЗ України”, м.Тернопіль, Україна Реферат Проведено дослідження ефективності реабілітаційних програм у хворих первинним гонартрозом з явищами остеопенії та остеопорозу. В дослідження включено 132 пацієнти з первинним гонартрозом (ПГА) зі зниженою щільністю кісткової тканини без синовіту, середній вік (61,18±0,74) р., тривалість захворювання (10,07±0,43) р., методом денситометрії у 97 пацієнтів визначено остеопенію, у 35 – остеопороз. Пацієнти були розподілені на 5 груп в залежності від методики застосування сірководневої бальнеотерапії та пелоїдотерапії. З’ясовано, що достовірно позитивний вплив на артрологічний статус, маркери кісткового метаболізму (паратгормон, лужну фосфатазу), цитокіни (IL-1β, ФНП-α, ІL-10) та показники периферичної гемодинаміки мали реабілітаційні програми з включенням різних варіантів сірководневої бальнеотерапії та низькотемпературної пелоїдотерапії. При застосуванні в лікувальному комплексі аплікацій пелоїдотерапії температурою 38-400С не спостерігалось позитивної динаміки артрологічного статусу: збільшення больового синдрому було відмічено у 28 % пацієнтів досліджуваної групи, обмеження рухів в суглобах у 32 %, зниження повсякденної активності у 44 %, у 22 % не було змін показників артрологічного статусу, покращення досліджуваних показників стану суглобів було відмічено лише у 18 % пацієнтів. Досліджувані цитокіни в цій групі не мали достовірних змін, а показники периферичної гемодинаміки не мали тенденції до покращення. Наші дослідження свідчать про доцільність застосування різних варіантів сірководневої бальнеотерапії в поєднанні з низькотемпературною пелоїдотерпаією для оптимізації реабілітації в санаторних умовах хворих первинним гонартрозом зі зниженною щільністю кісткової тканини. Ключові слова: остеоартроз, остеопороз, пелоїдотерапія, сірководнева бальнеотерапія, цитокіни. THE REHABILITATION PROGRAMS OPTIMIZATION IN SANATORIUM IN PATIENTS WITH PRIMARY GONARTHROSIS WITH DECREASING OF BONE MINERAL DENSITY T. G. Bakalyuk I.Ya. Gorbachevsky Ternopil State Medical University, Ternopil, Ukraine Abstract Objective of the study - pathogenetic rationale for the use of natural methods in the treatment of osteoarthritis in patients with reduced bone density in sanatorium conditions, to find out the effectiveness of the optimized rehabilitation programs. The study included 132 patients with primary gonarthrosis (PHAs) with low bone density (97 patients - osteopenia, 35 - osteoporosis), without synovitis, the average age (61,18 ± 0,74) years, duration of illness (10,07 ± 0,43) years. Visual analogue scale, a questionnaire to determine functional index Lequesne and WOMAC questionnaire were used to assess the arthrological status. The amount of active and passive movements in the joint evaluated in degrees using the protractor. The peripheral hemodynamics was investigated by tetrapolar rheovasography. The study tested blood serum mineral metabolism (total content of calcium and inorganic phosphorus), markers of bone formation (alkaline phosphatase, parathyroid hormone), proinflammatory cytokines IL-1β, TNF-α and anti-inflammatory cytokine IL-10 (pg / ml). Patients were distributed by randomization into 5 groups according to the methods of application of hydrogen sulfide balneotherapy and pelotherapy. It has been established that the rehabilitation program with inclusion of different options of hydrogen sulfide balneotherapy and low-temperature pelotherapy had significantly (p<0.05) positive effect on arthrologic status, parathyroid hormone, alkaline phosphatase, IL-1β, IL-10 and on the performance of peripheral hemodynamics. The use of pelotherapy applications temperature 38-40°C in the rehabilitation complex had negative dynamics of arthrologic status due to the increase pain in 28 % of patients in the study group, restriction of movements in the knee joints in 32 %, daily activity reduction in 44 %, unchanged artrological status in 22%, only 18% patients of this group marked improvement of studied indicators of joints. IL-1β, IL-10 in this group have not changed significantly, and peripheral hemodynamics did not have a tendency to improve. Since a significant role in the pathogenesis of osteoarthritis and osteoporosis belong to low-intensity systemic inflammation, the use of optimized schemes of the hydrogen sulphide balneotherapy with inclusion of inhaled hydrogen sulfide and water pelotherapy of low temperature activates the inflammatory process, as opposed to peloids applications temperature of 38-40°C. Regardless of the application and peloids appliqués temperature of 18-200C under the influence of the hydrogen sulphide balneotherapy IL-1β level was significantly reduced (p<0.05), increased levels of IL-10, which indicates a decrease in the activity of the inflammatory process and slow the progression of degradation of articular cartilage. Key words: osteoarthritis, osteoporosis, peloidotherapy, sulfide balneotherapy, cytokines. ОПТИМИЗАЦИЯ РЕАБИЛИТАЦИОННЫХ ПРОГРАММ В САНАТОРНЫХ УСЛОВИЯХ У ПАЦИЕНТОВ ПЕРВИЧНЫМ ГОНАРТРОЗОМ СО СНИЖЕННОЙ МИНЕРАЛЬНОЙ ПЛОТНОСТЬЮ КОСТНОЙ ТКАНИ Т. Г. Бакалюк ГВУЗ "Тернопольский государственный медицинский университет имени И. Я. Горбачевского МОЗ Украины ", г.Тернополь, Украина Реферат Цель исследования - патогенетическое обоснование применения природных методов в лечении больных остеоартрозом со сниженной плотностью костной ткани в санаторных условиях, выяснить эффективность применения оптимизированных реабилитационных программ. В исследование включено 132 пациента с первичным гонартрозом (ПГА) с пониженной плотностью костной ткани (у 97 пациентов - остеопения, 35 – остеопороз), без синовита, средний возраст (61,18 ± 0,74) лет, продолжительность заболевания (10,07 ± 0,43) лет. Для оценки артрологического статуса была использована визуальная аналоговая шкала, анкета для определения альгофункционального индекса Lequesne и опросник WOMAC. Объем активных и пассивных движений в суставе оценивали в градусах с помощью угломера. Периферическая гемодинамика исследовалась методом тетраполярной реовазографии. В сыворотке крови определяли показатели минерального обмена (содержание общего кальция и неорганического фосфора), маркеры костеобразования (щелочная фосфатаза, паратгормон), провоспалительные цитокины IL-1β, ФНО-α и противовоспалительный цитокин IL-10 (в пг/мл). Пациенты были распределены методом рандомизации на 5 групп в зависимости от методики применения сероводородной бальнеотерапии и пелоидотерапии. Установлено, что достоверно (р<0,05) положительное влияние на артрологический статус, паратгормон, щелочную фосфатазу, IL-1β, IL-10 и на показатели периферической гемодинамики имели реабилитационные программы с включением различных вариантов сероводородной бальнеотерапии и низкотемпературной пелоидотерапии. Применение в лечебном комплексе аппликаций пелоидотерапии температурой 38-400С имело негативную динамику артрологического статуса за счет увеличения болевого синдрома у 28 % пациентов исследуемой группы, ограничения движений в коленных суставах у 32 %, снижение повседневной активности у 44%, без изменений артрологического статуса у 22 %, только у 18 % отмечалось улучшение исследуемых показателей состояния суставов. IL-1β, IL-10 в этой группе изменялись не достоверно, а периферическая гемодинамика не имела тенденции к улучшению. Поскольку в патогенезе остеоартроза и остеопороза значительное место принадлежит низкоинтенсивному системному воспалению, применение оптимизированных схем сероводородной бальнеотерапии с включением ингаляций сероводородной воды и пелоидотерапии низкой температуры не активирует воспалительный процесс, в отличие от аппликаций пелоидов температурой 38-400С. Под влиянием сероводородной бальнеотерапии независимо от варианта применения и аппликаций пелоидов температурой 18-200С достоверно (р<0,05 ) снижается уровень IL-1β, и повышается уровень IL-10, что свидетельствует о снижении активности воспалительного процесса и замедление прогрессирования деструкции суставного хряща. Ключевые слова: остеоартроз, остеопороз, пелоидотерапия, сульфидная бальнеотерапия, цитокины.